An Economic Model of the Evolution of Food Retail and Supply Chains from Traditional Shops to Supermarkets to E-Commerce. (21st August 2018) - Lu, Liang; Reardon, Thomas
Abstract: Food retail has been in continuous evolution for the past century—both in developing and developed countries—from local traditional stores to supermarkets to e-commerce. In this paper we analyze the evolution of food retail by building a store choice equilibrium model and providing an illustrated discussion. The patterns in retail in any given time and place of different types of stores (such as traditional shops, supermarkets, and online e-commerce) depend on two main factors. The first are consumers' characteristics such as income, tastes, and travel costs of going to different stores and/or shipping costs if purchasing online. The second are the stores' cost structures, which include item costs from upstream producers, the costs of procurement supply chains (beyond the cost of the item) for perishable items, and the costs of in-store storage. We show under what conditions in equilibrium the different retail types exist and which can become dominant, and what types of goods (dry packaged foods versus perishables) are distributed by what type of retailers.